Comparative Analysis of Pesticide Use Determinants Among Smallholder Farmers From Costa Rica and Uganda - Staudacher, Philipp (2020)
Se seleccionó la licencia Creative Commons para este envío. El documento trae lo siguiente:Creative Commons Non Commercial CC BY-NC: This article is distributed under the terms of the Creative Commons Attribution-NonCommercial 4.0 License (https://creativecommons.org/licenses/by-nc/4.0/) which permits non-commercial use, reproduction and distribution of the work without further permission provided the original work is attributed as specified on the SAGE and Open Access pages (https://us.sagepub.com/en-us/nam/open-access-at-sage).